Evaluation of Antiacne Patch Preparations from a Combination of Lemon Juice (Citrus limon L.) and Ethanol Extract of Pure Honey (Honey bee) - Nadya Tsurayya; Ubaydullah Choir; Agus Kurniawan; Isnani Handayanti (Faculty of Mathematic and Natural Science, Garut University, 2026)
Acne vulgaris is one of the most common dermatological diseases, affecting individuals of all ages, particularly during adolescence. One of the causes of acne vulgaris is the bacterium Cutibacterium acnes. Acne vulgaris is usually characterized by comedones, papules, pustules, or nodules. Factors influencing acne include genetics, psychological factors, hormones, bacterial infection, and sebaceous gland activity. One regularly used treatment for acne vulgaris is acne patches. With the aid of natural ingredients such as lemon juice and pure honey, an alternative treatment for acne vulgaris can be developed. Lemon juice (Citrus limon L.) can be utilized as an antibacterial agent against Cutibacterium acnes due to its flavonoid content, which has biological activity as an antibacterial. Meanwhile, pure honey (Honey bee) is an antioxidant that can kill bacteria and germs, causing itchy acne on the skin, and can help fade acne scars. The study employed a laboratory experimental design. This research aimed to formulate an anti-acne patch preparation containing a combination of lemon juice (Citrus limon L.) and an ethanol extract of pure honey (Honey bee) that would exhibit good physical stability. Evaluation of the anti-acne patch preparation included organoleptic tests, pH, weight uniformity, patch thickness, moisture absorption, and antibacterial activity tests against Cutibacterium acnes using the disk diffusion method. The results indicated that the anti-acne patch exhibited favorable physical properties. The combination of lemon juice and ethanol extract of pure honey enhanced antibacterial activity against Cutibacterium acnes. The antibacterial activity test results showed that the combination of lemon juice and ethanol extract of pure honey in the anti-acne patch at a concentration of 14% had the highest antibacterial activity, with an inhibition zone diameter of 51.38 mm.